Moderasi Beragama Perspektif Ahmad Syafii Maarif dan Implementasinya Pada Kurikulum Pendidikan Agama Islam - Muhamad Yusuf; Syahrullah Syahrullah; Siti Uswatun Khasanah (Universitas Indraprasta PGRI, 2026)
Religious moderation is seen as an important concept in facing the challenges of the times marked by the strengthening of extremism, intolerance, and social division. This study examines Ahmad Syafii Maarif's thoughts on religious moderation and their relevance to implementation in the Islamic Religious Education (PAI) curriculum. Ahmad Syafii Maarif offers a view of moderation rooted in universal Islamic values, such as justice, humanity, tolerance, and respect for diversity as sunnatullah. His thoughts are not only oriented towards religious discourse, but also towards efforts to build a peaceful and inclusive national life. The research method used is qualitative with a library research approach. Primary data were obtained from Ahmad Syafii Maarif's writings, ideas, and thoughts, while secondary data came from literature related to religious moderation, Islamic education, and PAI curriculum documents. Data analysis was carried out using content analysis techniques to examine, interpret, and link the idea of ​​religious moderation with the objectives and implementation of the PAI curriculum. The research results show that religious moderation, according to Ahmad Syafii Maarif, emphasizes a balance between religious practice and respect for differences, strengthening humanitarian ethics, and rejecting all forms of violence and discrimination. This concept is highly relevant to the Islamic Religious Education (PAI) curriculum, which aims to shape students who are faithful, pious, and have noble morals, and who are able to live harmoniously in a pluralistic society.